Astragalus Polysaccharide Protect against Cadmium-Induced Cytotoxicity through the MDA5/NF-κB Pathway in Chicken Peripheral Blood Lymphocytes - Wanqiu Xie; Ming Ge; Guangxing Li; Linan Zhang; Zequn Tang; Ruyue Li; Ruili Zhang (Molecules, 2017)
Cadmium (Cd) is a known environmental pollutant that is associated with inflammation, oxidative stress, and cell apoptosis. Astragalus polysaccharide (APS) is a major component of Astragalus membranaceus, a vital qi-reinforcing herb medicine with favorable immuneregulation properties. To study the effect of APS on the inhibition of the cadmium-induced injury of peripheral blood lymphocytes (PBLs) in chickens through the MDA5/NF-κB signaling pathway, PLBs acquired from 15-day-old chickens were divided into control group, Cd group, APS + Cd group, anti-MDA5 mAb + Cd group, BAY 11-7082 (a nuclear factor kappa-light chain-enhancer of activated B cells [NF-κB] inhibitor) +Cd group, APS group, anti-MDA5 mAb group, and BAY 11-7082 group. The transcription levels of melanoma differentiation-associated gene 5 (MDA5), interferon promoter-stimulating factor 1 (IPS-1), NF-κB, and inflammatory factors tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 were measured by quantitative real-time PCR. MDA5 protein expression was measured by western blotting. Levels of malondialdehyde (MDA), glutathione peroxidase (GSH-Px), and superoxide dismutase (SOD) were measured by corresponding antioxidant kit. The morphological change of PBLs was measured by transmission electron microscopy. The results showed that Cd significantly increased the expression of MDA5, IPS-1, NF-κB, and their downstream cytokines, IL-1β and TNF-α, IL-6 in PLBs. In addition, a high level of MDA was observed in the Cd treatment group; the activities of GSH-Px and SOD were significantly lower in the Cd treatment group than those in controls (p < 0.05). Ultrastructural changes of PBLs showed that Cd promoted autophagy, apoptosis, and necrosis in PBLs. However, APS can efficiently improve Cd-induced cell damage by decreasing the activation of the MDA5 signaling pathway. The effect is consistent with that of anti-MDA5 mAb or/and BAY. The results indicated that APS inhibited Cd-induced cytotoxicity through the regulation of MDA5/NF-κB signaling.